Imaging Evaluation of Local Treatments for Foxed Papers - Matos, Marta (2018)
Foxing stains have been a sensitive problem to paper conservators. One of the most complicated decisions is whether to remove these foxing stains. The decision to bleach involves pondering on the aesthetic gain of the artwork’s visibility, versus the somewhat deleterious effect on the ageing properties of its paper support. This study evaluates the effect of local application of three bleaching agents in three different paper sample batches. The agents used were hydrogen peroxide, sodium permanganate and sodium borohydride. So far, the bleaching agent that showed the best overall results for all the papers was hydrogen peroxide.